Creep resistance in doubly crosslinked dynamic covalent networks - Mondal, Swagata; Wong, Alexander J.; Wagh, Mahendra A.; Alperstein, Lily; Sanjayan, Gangadhar J.; Sumerlin, Brent S. (POLYMER CHEMISTRY, 2024)
Vitrimers are a unique class of thermosets that demonstrate reprocessability and recyclability due to dynamic bond exchange at crosslinking sites. However, the same dynamic bond exchange predisposes vitrimers to macroscopic deformation and creep under constant stress, which limits many practical applications. Herein, we demonstrated that the incorporation of Janus-faced guanine-cytosine diamine (GCBDam) functionality within vinylogous urethane vitrimers leads to significant creep resistance due to network reinforcement via hydrogen bonding. The supramolecular associations of the GCBDam groups retarded stress relaxation at temperatures as high as 160 degrees C. Further, rheological data suggested that the cooperative nature of the bifunctional Janus-faced hydrogen bonding moieties allowed the GCBDam to act as ``stickers'' within the dynamic covalent networks. These results indicate that incorporating the bifunctional supramolecular moiety improved dimensional stability while conserving the hallmark vitrimer property of reprocessability. This work demonstrates that incorporating Janus-faced supramolecular moieties in vinylogous urethane vitrimers improved dimensional stability while conserving the hallmark vitrimer property of reprocessability.